MRI signs of anterior cruciate ligament graft restructuring in bone canal - Krasnoperov, Sergey; Golovakha, Maksim; Sheveliev, Oleksii (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
One of the reason for succeed anterior cruciate ligament reconstruction is the process of graft remodeling on the border «tendon-bone» in the bone canal. This factor can influence on the mechanical stability of the knee joint after anterior cruciate ligament reconstruction and can determine the rehabilitation exercises. Objective: to work out MRI criteria of graft reconstruction in bone canals. Methods: we included 90 patients, who were divided into two groups: the 1st o ne ( 47) w e used the technique «all-inside», in the 2nd group (43) — cross transtibial drilling technique. In 8 patients MRI was made. Results: we suggested the next criteria for the assessment of graft reconstruction in femoral and tibia bone canals: 1) signs of reconstruction on the border «tendon-bone»; 2) synovial fluid in the bone canals; 3) femoral and tibia bone marrow edema. Number of patients with the 1st stage (full graft reconstruction) without synovial fluid in bone canal increased in follow up period 3 to 9 months. Number of patients without bone marrow edema increased in follow up 3 to 12 months (35,6; 54,4; 74,5 and 84,5 %). It was shown in 6 months that in the 1st group there was a prevalence of patients (60 %) with the 1st stage of reconstruction compare with the 2nd group (42,2 %). As for the presence of synovial fluid in bone canal we observed a reliable difference in 3 months — 75,5 % in the 1st group compare with 78,9 % — in the 2nd. Conclusions: the dynamic of the graft reconstruction gets on the top till 9 months after surgery and after remains unchanged. The technique «all-inside» contributes faster and more qualitative graft reconstruction due to fewer trauma to the proximal part of the tibia and absence of screws in the tibia canal.